(untitled) (Economics and region, 2021)
There is unprecedented growth of service industry in the past few decades. In order to win the competition, a service company needs to have more opportunities (scope of activities). There is a need for a comprehensive assessment of competing service companies by different characteristics. Purpose of the article is to offer a method of integrated assessment of objects of marketing services for a set of components that characterize the scope of activities. The used method of integrated evaluation makes it possible to assess the competitiveness of companies, the quality of customer service and other objects of marketing in the service sector on a set of indicators.